Retroperitoneal Teratoma in an Infant: Case Report - Karikalan, Barani; Pasupati, Thanikachalam Meenakshi (Annals of Pathology and Laboratory Medicine, 2019)
Common location of teratomas in children are sacrococcygeal, gonadal, mediastinal and retroperitoneal, but teratomas may also occur at very unusual locations. A one-year-old girl presented with a large swelling at her left abdomen. Clinical examination revealed a solitary, non-tender, soft to firm, irregular cystic mass, occupying her left abdominal region. Computed Tomography (CT) scan finding was consistent with retroperitoneal teratoma. Complete surgical excision of the tumour was done without any difficulties. Histology of the excised tumour was conclusive of mature cystic teratoma.